2017
DOI: 10.1108/f-12-2015-0092
|View full text |Cite
|
Sign up to set email alerts
|

Green Star is not a physical activity star

Abstract: Purpose The purpose of this paper is to report on research investigating the relationship between physical activity and workplace design. In particular, the paper explores the social–ecological context of a new workplace building. This paper seeks to understand why better physical activity outcomes for the staff were not observed in the new building despite influence from a staff wellness committee during design; achieving success against existing best-practice indicators; and staff reporting increased feeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Another reason people move about an office is to talk to colleagues. A recent study in which office workers were relocated to a new building showed that expectations of quietness in the new building discouraged short non sedentary breaks in workflow occasioned by getting up to talk to colleagues or standing about having casual chats at colleagues' desk [55].…”
Section: Socio-cultural Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Another reason people move about an office is to talk to colleagues. A recent study in which office workers were relocated to a new building showed that expectations of quietness in the new building discouraged short non sedentary breaks in workflow occasioned by getting up to talk to colleagues or standing about having casual chats at colleagues' desk [55].…”
Section: Socio-cultural Factorsmentioning
confidence: 99%
“…There has been little research on the impact of building design on physical activity and sedentary behaviour of office workers [55,62]. Building design and floor layout can indirectly shape the organisation of work and the opportunities for incidental physical activity at work [63].…”
Section: Building Design and Layoutmentioning
confidence: 99%
See 3 more Smart Citations